(untitled) (Brazilian Journal of Radiation Sciences, 2022)
Radiation protection is a term applied to concepts, requirements, technologies and operations related to protection of people against the harmful effects of ionizing radiation. Strategic Environmental Assessment is an appropriate environmental impact assessment instrument to establish whether or not a policy, plan or program can be developed and under which conditions. The objective of this work is to demonstrate and evaluate the use of the Strategic Environmental Assessment associated with radiation protection, through the contribution of the scientific community linked to the nuclear area. Therefore, we systematically review the literature using the references of documents stored in the International Nuclear Information System database concerning Strategic Environmental Assessment and Radiation Protection. We also used the two most numerous sets of different types of documents to apply a methodology for qualitative data analysis using a meta-analysis software to infer the importance tendency of themes through the frequency of words. Conclusions pointed out in this research are that it is not possible to relate the production of articles to scientific journals with the production of no other type of scientific or technical literature at the moment. Future studies can check whether the number of reports produced may turn out to be relevant articles or not. And the primordial process by which researchers obtain information about the work of their peers is through articles and we conclude that this number is small.